Geochemistry of northwestern Saveh magmatic complex (Markazi province) - Mohammad Reza Emami Meybodi; Nahid Naseri; Reza Zarei Sahamieh; Khadijeh Momeni Zafarabad; Ahmad Ahmadi Khalaji (Journal of Economic Geology, 2021)
Introduction Considering the wide extent of the Urumieh-Dokhtar magmatic arc and the presence of many intrusive and volcanic rocks in this belt, an important question from scientific and exploration points of view is “Why are some plutons productive whereas others are sub-productive and/or barren?” Barren and productive magmatic systems related to calc-alkaline arc magmatism are identified as normal or non-adakitic (low Sr/Y<20) and adakitic (high Sr/Y>20) magmas, respectively. Barren magmas are non-mineralized and have a low Sr/Y ratio, while high Sr/Y magmas are responsible for Cu-mineralization and are known as productive magmas that occur in all major orogenic belts worldwide (Cooke et al., 2005). Understanding their origin and petrogenesis is of critical importance to decipher their long-term growth and stabilization of the continental crust, and formation of economically valuable ore deposits (Monecke et al., 2018). Barren granitoid magmas typically form in pre-collisional subduction zone environments (Shahabpour, 1992), which is confirmed by the results obtained in this study. Magmatism in this region began in the Early Eocene and continued until the Pliocene. The volcanic and intrusive barren-type rocks (Eocene) that formed in a subduction-related tectonic setting are characterized by calc-alkaline and tholeiitic geochemical signature (Shahabpour, 2005). The northwest of Saveh magmatic complex is situated at the central part of the Urumieh-Dokhtar magmatic belt. The volcanic rocks of northwest of Saveh are crosscut by Late Eocene-Early Oligocene granitoids that are exposed over an area of about 100 km2.